Kirana lens / Nur Alyaa Insyirah Muhamad Shaharudin - Muhamad Shaharudin, Nur Alyaa Insyirah (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
This study summarizes the new design and rebranding of Kirana Lens, a product that Manja Rose owns and was rebranded from Sutera Lens. Bangi, Selangor, saw its establishment in 2019. The main issue was that the packaging and logo did not represent the core of a contact lens product, which was a disconnect. As a result, a thorough redesign project was started to bring the packaging and logo into line with the brand's identity.The updated package and logo were painstakingly created to emphasize the three main qualities of contact lenses: beauty, brightness, and clarity. The goal of this design was to create a visual identity that accurately reflected the product. By showcasing its eye-catching color scheme, the new slogan "Seindah Warna, Pandangan Sempurna" better captured the spirit of Kirana Lens.A set of grayscale advertisements was created with the purpose of enhancing the overall marketing strategy through the smart use of selective colorization. The visual impact aimed to highlight the variety and striking color options provided by Kirana Lens, which is designed for women and teenagers. Kirana Lens unveils three stunning new colors, which are Kencana (brown), Nilangsuka (cyan), and Nilakandi (blue).The majority of the elements in the design have a grayscale theme, and color is only sparingly incorporated into the eyes and select designs. Every shade is designed to go well with a variety of personalities and styles, giving wearers a wide range of stylish options. This abstract sheds light on the tactical choices and artistic interpretations that drove the branding campaign and made Kirana Lens a product that is instantly recognizable as being exquisitely designed. By addressing issues with visual representation, the all-encompassing strategy established Kirana Lens as a strong option in the highly competitive contact lens market.This idea of contrast is applied to print advertisements, digital graphics, and business products, guaranteeing consistency across multiple channels. Corporate apparel, uniforms, and merchandising, among other things, are made to embody the contrast and emphasize idea. Print advertisements comprise five auxiliary marketing techniques in addition to the main advertisements, which include magazine ads, billboards, outdoor banners, and subway posters. The website, exhibits, and TV ads are all covered by digital design components. In conclusion, the redesigned Kirana Lens revitalizes the long-standing Sutera Lens brand with its eye-catching color and cozy soft contact lenses.